Patriarch Bartholomew’s position towards the war against Ukraine - Hrimle, Patrice (War in Ukraine, 2025)
This article highlights the statements of the Greek-speaking Orthodox Churches up to the beginning of 2023, especially those of Ecumenical Patriarch Bartholomew, which are related to the war against Ukraine. As a religious leader, the patriarch drew attention to this war and thereby contributed to the public discourse on this matter. His anti-war appeals to stop the military annihilation of Ukraine and the genocide of its people stand out among other public figures. In addition, the author outlines some efforts of the Ecumenical Patriarch in interchurch relations, particularly concerning the Russian Orthodox Church. The text takes a closer look at Bartholomew’s reflections on the nature of war, its origins, consequences and possible solutions. Furthermore, the author focuses on the reaction of the Ecumenical Patriarch to the siege of Mariupol, i. e., to the consequences of the Russian air force’s bombing of the city, especially the casualties of the civilian population as well as damages inflicted on the historical and cultural heritage of ethnic Greeks.